International standards on auditing (ISAs) adoption: An institutional perspective - Ahmed Eltweri; Alessio Faccia; Scott Foster (Administrative Sciences, 2022)
This study seeks to examine the factors that influence the adoption of ISAs, intending to stimulate establishing a responsible and efficient auditing regime in Libyan auditing practice, shedding light on challenges in auditing practices in the North African region. This study conducted semi-structured interviews with 43 participants that represented 5 key actors from within the auditing field in Libya, including preparers and users of annual reports. Regarding ISAs adoption, the study focused on those institutional isomorphism drivers that are found to produce a greater impact on the experience of auditing practice in Libya. The identified factors are (a) foreign corporations, such as accountancy firms, (b) economic systems and the stock market, (c) international financial institutions (IFIs), and (d) the legal system. The research demonstrated that these drivers systematically and consistently predict the level of ISAs adoption commitment and associated harmonisation. Given the growing interest in harmonising auditing practice not only by scholars but also by policy and decision-makers, the relevance of this research cannot be questioned since it addresses significant concerns and contributes to the development of an under-researched topic in Africa. This paper expands the literature on the importance of harmonising auditing practices and provides fresh insights into auditing practices in a politically unstable country. Awareness is also raised about the most relevant drivers of adopting ISAs and several implications for policymakers and regulators in pursuing international harmonisation of auditing standards.
Keywords: 350; emerging economies; auditing environment; institutional theory; international institutions and firms; laws and regulations